Strategi Pengembangan Sumber Daya Manusia dalam Disrupsi Teknologi Informasi - Rahman, Fikri Aulia; Jaelani, Jaelani; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
The era of globalization has had a significant impact on various aspects of life. The current era of globalization demands that everyone possesses abilities in line with the developments of the times. Massive changes caused by innovations that transform business systems and structures to a newer level are known as the Era of Disruption. The Disruption Era can also be interpreted as the period of transitioning from manual to fully digital processes. In the era of disruption, drastic changes occur that alter the human way of life in various fields. The world's shift towards digital disruption is unavoidable for every individual, especially with the impending Fourth Industrial Revolution and the move towards the 5.0 era, demanding new business skills and ways of working. One crucial aspect in facing this revolution is how to develop human resources (HR) to meet the demands of the time. This research aims to describe, analyze, and assess human resource development strategies in facing challenges in the era of information technology disruption. The research utilizes a literature review methodology with a descriptive analysis approach. The findings indicate that comprehensive and appropriate strategies for human resource development in the face of information technology disruption are not only necessary but imperative and highly essential. The research findings suggest that creative and deeply skilled human resources are crucial to ensuring the sustainability of workforce competitiveness. Knowledge and skills embedded in individuals regarding information technology development are excellent seeds that will drive innovation, productivity, and progress